Thermosensitive hydrogels loaded with human‐induced pluripotent stem cells overexpressing growth differentiation factor‐5 ameliorate intervertebral disc degeneration in rats. Issue 5 (12th January 2020) - Hu, Annan; Xing, Rong; Jiang, Libo; Li, Zefang; Liu, Peng; Wang, Houlei; Li, Xilei; Dong, Jian
Abstract: To evaluate the effects of thermosensitive hydrogels loaded with human‐induced pluripotent stem cells transfected with the growth differentiation factor‐5 (GDF5‐hiPSCs) on rat intervertebral disc regeneration. GDF5‐hiPSCs were cocultured with rat nucleus pulposus (NP) cells in vitro. Real‐time PCR and western blot were used to determine the differentiation of hiPSCs. Rat caudal intervertebral discs were punctured using a needle under X‐ray, and groups of coccygeal (Co) discs were subject to various treatments: Puncture group (Co6/7, punctured without treatment); Hydrogel group (Co7/8, 2 μl of hydrogel injected without cells); GDF5‐hiPSCs + Hydrogel group (Co8/9, 2 μl of GDF5‐hiPSCs‐loaded hydrogel injected); and Normal control (Co5/6). X‐ray, MRI, and histological evaluations were performed at 1, 2, and 3 months after cell transplantation and relative changes in the disc height index (DHI%) and voxel count were calculated and compared. GDF5‐hiPSCs were successfully differentiated to a chondrogenic linage after cocultured with rat NP cells. In terms of X‐ray, MRI, and HE staining scores, the GDF5‐hiPSCs + Hydrogel group was significantly superior to the Puncture and Hydrogel groups ( p < .05). Compared with the Normal group, the MRI‐based voxel count of the GDF5‐hiPSCs + Hydrogel group was significantly lower at 1, 2, and 3 months after cell transplantation ( p < .05). However, there were no significant differences in histological scores at 1 and 2 months after cell transplantation compared with the Normal group ( p > .05). In conclusion, thermosensitive hydrogel‐encapsulated hiPSCs overexpressing the GDF5 gene ameliorated intervertebral disc degeneration.